Diagnostic accuracy and validation of 18F-fluorodeoxyglucose positron emission tomography scores in a large cohort of patients with polymyalgia rheumatica - Moreel, Lien; Boeckxstaens, Lennert; Betrains, Albrecht; Van Hemelen, Maarten; Vanderschueren, Steven; Van Laere, Koen; Blockmans, Daniel (Frontiers in Medicine, 2022)
Background: Several studies have shown that 18F-FDG PET may contribute to the diagnosis of polymyalgia rheumatica (PMR). Previously, we developed a composite PET score called the Leuven score, which was recently adapted to the more concise Leuven/Groningen score. The aim of this study is to validate and compare the diagnostic accuracy and cut-off points of both scores in a large cohort of PMR patients. Methods: Patients with a possible clinical diagnosis of PMR and a PET scan prior to the initiation of glucocorticoids between 2003-2020 were included retrospectively. The gold standard for the diagnosis of PMR was the judgment of two experienced clinicians after a follow-up of at least 6 months. FDG uptake was scored visually in 12 articular regions (scores 0-2) and a total skeletal score was calculated by summing the individual scores. Results: 162 patients with PMR and 83 control patients were included. Both PET scores showed high diagnostic accuracy in the ROC analysis (area under the curve 0.986 and 0.980 respectively). The Leuven Score provided a sensitivity of 91.4% and specificity of 97.6% at its predefined cut-off point of 16. With the newly determined cut-off point of 12 the sensitivity was 98.8% and specificity 95.2%. The Leuven/Groningen score had a sensitivity and specificity of 93.2% and 95.2%, respectively, with the prespecified cut-off point of 8, and 96.9% and 92.8% with the optimal cut-off point of 7. Conclusion: The original Leuven score and the simplified Leuven/Groningen score both had excellent diagnostic accuracy.